Hedging against disaster: Risk and mitigation in the media and entertainment industries. (1st June 2018) - Chalaby, Jean K.
The objective of this article is twofold. First, it seeks to identify and classify the most likely sources of potential loss for media and entertainment businesses. Adopting the World Bank's definition of risk as a 'possibility of loss' and opportunity as the 'upside of risk', this article constructs a typology of risks that are categorized in seven types: catastrophic, financial, regulatory, technological, intellectual property (IP) related, value chain related and commercial. Combining this typology with a review of the most common risk mitigation strategies, this article demonstrates that risk management is central to the way media firms operate and has a determining influence on their output. Risk analysis, therefore, offers us a better understanding of corporate strategies in the media and entertainment industries both in terms of management and content.